Increasing Agricultural Sector Investment through Sectors and Regional Leading Products in Central Java Province - Suparmono Suparmono; Bunga Alfausta Amalia (Telaah Bisnis, 2024)
This article aims to analyze the advantages and competitiveness of agricultural sectors and sub-sectors that have advantages in the economy of Central Java Province. The analytical tools used to determine the leading sectors and sub-sectors are location quotient (LQ), Klassen Analysis, Shift Share Analysis, and Sectoral Typology. By using data from 2023, it was found that overall, most of the sub-fields in the agriculture, forestry and fisheries business sector of Central Java Province were categorized as competitive sectors. The subsector that is not categorized as competitive is food crops. The agriculture, forestry and fisheries sector is categorized as an advanced business field and its growth is very fast, but the forestry and logging, fisheries sub-sector has a slow growth speed but is a growing industry. The agriculture, livestock, hunting, and agricultural services sub-fields have very fast and advanced growth so that they can become regional superior potential. The commodities of food crops and plantation crops still need further attention because the speed of growth is still hampered, although the industry has potential and is developing.